MiR-509-3-5p-NONHSAT112228.2 Axis Regulates p21 and Suppresses Proliferation and Migration of Lung Cancer Cells - Liang, Jing-Jing; Wang, Jun-Yi; Zhang, Tong-Jia; An, Guo-Shun; Ni, Ju-Hua; Li, Shu-Yan; Jia, Hong-Ti (Current Topics in Medicinal Chemistry, 2020)
Background: Although the involvement of individual microRNA and lncRNA in the regulation of p21 expression has largely been evidenced, less is known about the roles of functional interactions between miRNAs and lncRNAs in p21 expression. Our previous work demonstrated that miR-509- 3-5p could block cancer cell growth. Methods: To gain an insight into the role of miR-509-3-5p in the regulation of p21 expression, we performed in silico prediction and showed that miR-509-3-5p might target the NONHSAT112228.2, a sense-overlapping lncRNA transcribed by a non-code gene overlapping with p21 gene. Mutation and luciferase report analysis suggested that miR-509-3-5p could target NONHSAT112228.2, thereby blocking its expression. Consistently, NONHSAT112228.2 expression was inversely correlated with both miR-509-3-5p and p21 expression in cancer cells. Ectopic expression of miR-509-3-5p and knockdown of NONHSAT112228.2 both promoted proliferation and migration of cancer cells. Results: Interestingly, high-expression of NONHSAT112228.2 accompanied by low-expression of p21 was observed in lung cancer tissues and associated with lower overall survival. Conclusion: Taken together, our study found a new regulatory pathway of p21, in which MiR-509-3-5p functionally interacts with NONHSAT112228.2 to release p21 expression. MiR-509-3-5p— NONHSAT112228.2 regulatory axis can inhibit the proliferation and migration of lung cancer cells.
Keywords: p21